Analysis of the Meshing Characteristic of Helical Gear based on Node Generation Technique - Feng Qiyin; Zhang Jun; Du Yuhong (Jixie chuandong)
Gear drive is used widely,and the probability of failure is very high.So it is very necessary to analyze the characteristic of the gear pair meshing.A method of using ANSYS APDL language node control technique to create the finite element model of helical gear is described,and an analysis example of using this modeling method is carried on.The distribution law of the stress and strain of the meshing process is clarified by analyzing.At the same time,the analysis of the influence of root fillet radius on the meshing character is carried out.The results show that the bending stress is decreased with the tooth root radius increases.